Use of ICTs by Extension Personnel in Dissemination of Agriculture Information in North Eastern Karnataka - K., Shashidhara K. (Indian Journal of Extension Education, 2020)
The study was conducted in North Eastern Karnataka and Raitha Samparka Kendraâ€™s (RSKs) of Kalaburgi,Â Yadgir and Raichur districts. 55.97 per cent of the extension personnel belonged to medium level of ICT usageÂ followed by low level (25.37%) and high level (18.66%) of usage. The extent of usage of ICT tools and services by the extension personnel in dissemination of agriculture information was positive and significantly correlated with the ICT services available (r=0.641), organization climate (r=0.475) and job commitment (r=0.591). LogitÂ regression analysis show that independent variables contribute to 82.80 per cent of the variation in usage of ICT tolls and services by extension personnel in dissemination of agriculture information.